Laparoscopic versus open reduction of idiopathic intussusception in children: an updated institutional experience - Jian Zhao; Jun Sun; Deyu Li; Wei Jue Xu (BMC, 2022)
Abstract Background In the reduction of intussusception, due to the lack of randomized, controlled, and prospective clinical trials to confirm the superiority of the laparoscopic approach over open surgery, more evidence was needed. This study aimed to compare the results of laparoscopy and open reduction of idiopathic intussusception in children as well as to illustrate some skills for the reduction of intussusception laparoscopically. Methods A retrospective review was performed to evaluate outcomes for patients with idiopathic intussusception who were treated laparoscopically (LAP group) from January 2015 to December 2019 and to compare the outcomes with laparotomy (OPEN group) during the same period. Results During the period studied, there were 162 patients treated surgically for intussusception: 62 LAP and 100 OPEN. No statistical differences were found in demographic data, clinical symptoms and signs, duration of symptoms, location and types of intussusception between the two groups. Conversion to open procedure was required for 11 patients in the LAP group. The operation time and time to oral intake were shorter in the LAP group while the difference was not significant. If the 11 conversion cases were excluded, the operation time and time to oral intake were significantly shorter (P < 0.05) in the LAP group. The length of stay was significantly shorter in the LAP group (P < 0.05). Intraoperative and postoperative complication rates between the two groups were comparable (P = 1.0). Conclusion Laparoscopy was safe and effective in the treatment of pediatric idiopathic intussusceptions. Pediatric surgeons with sophisticated minimally invasive skills should choose laparoscopy as the first choice in the treatment of idiopathic intussusceptions.